Challenges and Management Strategies for Mediterranean Cork Oak Forests: Impacts of Climate Change, Human Activities, and Invasive Species – A Review - Mesfin Boja; Kaouther Mechergui; Wahbi Jaouadi; Youssef Ammari (Sustainability Science and Resources, 2025)
The Mediterranean cork oak (Quercus suber) forests, crucial for maintaining biodiversity and supporting local economies, are experiencing severe and multifaceted declines driven by an array of environmental and anthropogenic factors. These unique ecosystems are increasingly threatened by climate change, which is manifesting through more frequent and severe droughts, elevated temperatures, and unpredictable precipitation patterns. Such climatic shifts are not only affecting cork production but are also compromising the overall health and resilience of these forests. Concurrently, human activities, including extensive deforestation, overharvesting, and the conversion of forested lands into agricultural or urban areas, have intensified habitat fragmentation and disrupted natural processes essential for forest regeneration. The spread of invasive species, particularly Aleppo pine (Pinus halepensis), exacerbates these challenges by encroaching on traditional cork oak habitats. This intrusion alters forest composition, reduces biodiversity, and affects ecosystem functionality. Furthermore, diseases such as Phytophthora cinnamomi are playing a critical role in forest decline by attacking cork oak roots, impairing water and nutrient uptake, and contributing to soil degradation. The combined effects of these pressures result in a diminished capacity for natural regeneration and increased vulnerability of these forests to further disturbances. To counteract these threats, adaptive forest management practices are imperative. Selective thinning operations can enhance forest resilience by reducing competition for resources and improving water and carbon use efficiency. Reforestation efforts should focus on planting drought-resistant native species to better align with future climate conditions. Additionally, effective grazing management is essential to prevent soil degradation and maintain vegetative cover. Long-term monitoring and proactive management strategies are crucial for early detection and control of invasive species and diseases, which will help mitigate their impacts and support forest health. Sustainable land use practices, including the promotion of diverse tree species and the integration of indigenous plants, can bolster ecosystem resilience and support a robust soil trophic network. Engaging stakeholders and local communities in conservation efforts and raising awareness about sustainable forestry practices are vital for the successful implementation of these strategies. By adopting a comprehensive and coordinated approach, we can better safeguard the ecological integrity and economic value of Mediterranean cork oak forests, ensuring their sustainability for future generations.